Comparative pollen morphology of annual Trigonella L. (Fabaceae) in Turkey - Pinar, N. Munevver; Akan, Hasan; Ceter, Talip; Aytac, Zeki; Ekici, Murat; Acar, Aydan; Akdogan, Selin (Springer Science and Business Media LLC, 2013)
Pollen morphology of 38 Trigonella species was investigated with light microscopies and scanning electron microscopies. Pollen slides were prepared using Wodehouse technique. The pollen grains of Trigonella members are radially symmetrical and isopolar, their outlines are oblong in equatorial view and circular in polar view. Amb is semicircular. The pollen grains are prolate-spheroidal, oblate-spheroidal, suboblate, spheroidal, and prolate with the polar axes 13.5–49.9 μm and the equatorial axes 10.4–43.7 μm. The smallest dimensions are observed in T. spinosa and T. brachycarpa, and the largest in T. carica and T. rhytidocarpa. The pollen grains of Trigonella taxa are usually tricolporate or rarely tricolpate, pantocolporate, tetracolporate, and tricolpodiporate. Various ornamentation types were observed: Microreticulate (section Samaroideae, Pectinatae, Falcatulae, Cylindricae, Bucerates, Reflexae, Isthmocarpae, Capitatae and Foenum-graecum), rugulate-scabrate (section Lunatae, Uncinatae), perforate (T. halophila, T. rigida and T. carica from section Bucerates) and retipilatae (section Biebersteinianae) at equator region and psilate-perforate (section Samaroideae, Pectinatae, Bucerates, Reflexae, Isthmocarpae, Foenum-graecum, T. coelesyriaca, T. cilicica), rugulate-scabrate (section Lunatae, Uncinatae), microreticulate (Falcatulae, Cylindricae and Foenum-graecum) and retipilatae (section Biebersteinianae) at polar region. Ornamentations, pollen shape and the aperture type have been observed as important morphological characters.